Biofilm production of Pseudomonas spp. isolates from canine otitis in three different enrichment broths. Issue 3 (21st March 2019) - Robinson, Victoria H.; Paterson, Sue; Bennett, Cheryl; Steen, Stephen I.
Abstract : Background: Pseudomonas spp. are commonly isolated from dogs with clinical otitis and have been shown to produce biofilm. There is a paucity of studies demonstrating biofilm growth in veterinary medicine. Hypothesis/objectives: To compare biofilm production of Pseudomonas spp. isolated from dogs with otitis using three different enrichment broths at two different time points. Speciation was performed. Animals: One hundred isolates from 98 dogs with clinical otitis were assessed for biofilm production. Methods and materials: One hundred isolates were assessed for biofilm production using a microtitre plate assay. Biofilm production in Luria–Bertani Broth (LBB), Mueller–Hinton Broth (MHB) and Tryptic Soy Broth (TSB) were assessed after 18 and 24 h of incubation. Results: At 18 h, biofilm production was demonstrated in 87% of LBB, 91% of TSB and 93% of MHB grown isolates. By 24 h, this was 92% of LBB, 96% of TSB and 99% of MHB isolates. Biofilm production was significantly increased after 24 h incubation compared to 18 h. A significant difference was noted in biofilm production between LBB and MHB ( P  = 0.0349), but not between LBB and TSB ( P  = 0.3727) or MHB and TSB ( P  = 0.3687) at 24 h incubation. Two isolates were speciated as P. fluorescens and 98 as P. aeruginosa . Conclusion and clinical importance: Not all enrichment broths were equivalent to one another and 24 h incubation was superior to 18 h. Biofilm production was high in this population of Pseudomonas spp. isolates. Abstract : Background – Pseudomonas spp. are commonly isolated from dogs with clinical otitis and have been shown to produce biofilm. There is a paucity of studies demonstrating biofilm growth in veterinary medicine.Hypothesis/objectives – To compare biofilm production of Pseudomonas spp. isolated from dogs with otitis using three different enrichment broths at two different time points. Speciation was performed.Conclusion and clinical importance – Not all enrichment broths were equivalent with one another and 24 h incubation was superior to 18 h. Presence of a biofilm is likely in otic Pseudomonas spp. isolates.